2010
DOI: 10.1111/j.1399-0012.2010.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in sustaining hepatic outflow in left lobe but not right lobe living donor liver transplantation

Abstract: The middle and left hepatic veins tend to distort and stretch during graft regeneration. These characteristics seem to be associated with outflow disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…It has been previously demonstrated that the placement of a wide common channel portion is beneficial for accommodating potential graft remodeling-associated distortion of the hepatic vein anastomosis. [5][6][7] Therefore, when wedged unification is being performed, the depth of the wedging should be adjusted and optimized after the consideration of the relative sizes of the graft and the recipient's hepatic veins. At this point, we emphasize the importance of size matching between the graft hepatic vein orifice and the diameter of the recipient's IVC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously demonstrated that the placement of a wide common channel portion is beneficial for accommodating potential graft remodeling-associated distortion of the hepatic vein anastomosis. [5][6][7] Therefore, when wedged unification is being performed, the depth of the wedging should be adjusted and optimized after the consideration of the relative sizes of the graft and the recipient's hepatic veins. At this point, we emphasize the importance of size matching between the graft hepatic vein orifice and the diameter of the recipient's IVC.…”
Section: Discussionmentioning
confidence: 99%
“…17 To date, we have 3 technical approaches to bench work for hepatic vein orifices of left liver grafts for both adult and pediatric patients, including extended left livers, left livers without the MHV trunk, extended LLSs, LLSs, reduced LLSs, and monosegments. The first approach is unification venoplasty with central wedging/septoplasty to make a wide common channel [5][6][7] ; the second, the placement of a side patch to widen the hepatic vein orifice, 9,18 is a procedure that can be combined with the first approach; and the third is a very unusual combination of the first approach and vein graft interposition. According to our experience, these techniques cover nearly all hepatic vein variations in various types of left liver grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This again can cause a horizontal shift in the lie of the MHV and LHV resulting in kinks and outflow issues. 24 In contrast, the right-lobe graft resides comfortably in the limited right subphrenic cavity and regenerates toward the left and anteromedial sides with little positional change of the graft hepatic veins.…”
Section: Disadvantages Of Left-lobe Graftsmentioning
confidence: 99%
“…Once it occurs, the liver graft is impaired by congestion, which results in jaundice, massive ascites, coagulopathy, and occasionally hepatic failure. Outflow obstructions after liver transplantation are caused by strictures and/or torsion on the anastomosis of the hepatic vein to the inferior vena cava (IVC) 2. The incidence has been reported to be 2% to 7% in living donor liver transplantation (LDLT) 3‐5.…”
mentioning
confidence: 99%